Tucker Manufacturing Company; J. W. Black, Photograph Rooms - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of Tucker Manufacturing Company; J. W. Black, Photograph Rooms from the 1870 Boston City Directory